Chemical Modification of Lipase and its Immobilization on Polymer Beads for Use in Organic Synthesis - Basri, Mahiran (1993)
A simple and effective method to produce a more active, stable and practical lipase preparation was identified. Soluble lipase from Candida rugosa was modified with different types of hydrophobic chemical modifying reagents. The esterification activities of the modified lipases were enhanced following their modification. The degree of activity enhancement depends on the type and molecular weight of the modifiers used and the degree of modification of the enzyme.A lower degree of enzyme derivatization was required for modification with the high molecular weight modifiers to attain maximal activities. In the case of monomethoxypolyethyleneglycol (PEG), however, maximal activity was attained only after exhaustive modification. The opt imum esterificat ion temperature and preference of fatty acids as acyldonors of the modified lipases were very similar to those of the native enzyme. Both were more active in non-polarsolvents than in polarsolvents. The modified lipases showed higher thermostability, solvent stability and storage stability compared to the native lipase. The lipase modified with PEG 1900 was the most thermostable, and that modified with methyl 4-phenylbutyrimidate (imidoester VI) was the most stable when incubated in benzene for ten days. The bests to rage condition was at low temperature and in the lyophilized form.